2013
DOI: 10.1093/infdis/jit600
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of Type I Interferon Signaling Protects Mice Against Lethal Sepsis

Abstract: Current research on new therapeutic strategies for sepsis uses different animal models, such as the lipopolysaccharide-induced endotoxemia model and the cecal ligation and puncture (CLP) peritonitis model. By using genetic and pharmacologic inhibition of the type I interferon (IFN) receptor (IFNAR1), we show that type I IFN signaling plays a detrimental role in these sepsis models. Mortality after CLP was reduced even when type I IFN responses were blocked after the onset of sepsis. Our findings reveal that ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 47 publications
6
33
0
1
Order By: Relevance
“…These findings suggest that the subset of genes induced by signaling through the IFN-αR1 chain alone, independent of the IFN-αR2 chain, contribute more substantially to the pathogenesis of Gram-negative endotoxemia than the classical ISGs induced by signaling through conventional IFN-αR1/IFN-αR2 heterodimeric complexes. Furthermore, related studies by others showed that treatment with a neutralizing anti-IFN-αR1 mAb protects mice against development of endotoxin-induced lethality in 2 distinct murine models of Gram-negative septicemia [44]. Together, these studies suggest that blocking signaling through the IFN-αR1 chain, but not the IFN-αR2 chain, provides a useful therapeutic approach to the treatment of bacterial endotoxemia.…”
Section: Discussionmentioning
confidence: 97%
“…These findings suggest that the subset of genes induced by signaling through the IFN-αR1 chain alone, independent of the IFN-αR2 chain, contribute more substantially to the pathogenesis of Gram-negative endotoxemia than the classical ISGs induced by signaling through conventional IFN-αR1/IFN-αR2 heterodimeric complexes. Furthermore, related studies by others showed that treatment with a neutralizing anti-IFN-αR1 mAb protects mice against development of endotoxin-induced lethality in 2 distinct murine models of Gram-negative septicemia [44]. Together, these studies suggest that blocking signaling through the IFN-αR1 chain, but not the IFN-αR2 chain, provides a useful therapeutic approach to the treatment of bacterial endotoxemia.…”
Section: Discussionmentioning
confidence: 97%
“…Detrimental roles for IFN-␤ and/or its receptor IFNAR1 have been described during sepsis (15)(16)(17), bacterial infections including Listeria and Mycobacterium spp. (18), parasitic infections caused by Trypanosoma and Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%
“…Puerperal sepsis, a bacterial infection originating in the uterus following delivery, is the leading infectious cause of maternal death worldwide (26). Type I IFN signaling has been associated with increased severity of infection with a number of relevant pathogens, including staphylococcal and Pseudomonas species (27,28). Likewise, elevated levels of type I IFN are associated with pathogenesis of certain autoimmune diseases such as systemic lupus erythematosus (SLE) (29).…”
Section: Discussionmentioning
confidence: 99%